2013
DOI: 10.1097/scs.0b013e31826686d3
|View full text |Cite
|
Sign up to set email alerts
|

RUNX2 Quadruplication

Abstract: The RUNX2 transcription factor regulates osteoblast differentiation. Its absence, as with cleidocranial dysplasia, results in deficient bone formation. However, its excess seems to follow a dose response of over ossification. RUNX2 duplications (3 copies) are exceedingly rare but have been reported to cause craniosynostosis. There are no existing reports of quadruplications (4 copies). We present a case study of a boy with an atypical skull deformity with pan-craniosynostosis whose microarray analysis revealed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…RUNX2 deficiency results in deficient skull ossification in the context of cleidocranial dysplasia. Importantly, RUNX2 duplication [Mefford et al, 2010], triplication [Varvagiannis et al, 2013] and quadruplication [Greives et al, 2013] have been reported in patients with syndromic CS and there appears to be a direct correlation between the gene copy number and the severity of the phenotype. Our group identified two rare missense variants, M175R and R237C in two of 137 patients with sNCS.…”
Section: Genetic Etiopathogenesis Of Craniosynostosismentioning
confidence: 99%
“…RUNX2 deficiency results in deficient skull ossification in the context of cleidocranial dysplasia. Importantly, RUNX2 duplication [Mefford et al, 2010], triplication [Varvagiannis et al, 2013] and quadruplication [Greives et al, 2013] have been reported in patients with syndromic CS and there appears to be a direct correlation between the gene copy number and the severity of the phenotype. Our group identified two rare missense variants, M175R and R237C in two of 137 patients with sNCS.…”
Section: Genetic Etiopathogenesis Of Craniosynostosismentioning
confidence: 99%
“… 46 In craniosynostosis, additional copies of Runx2 have been detected in a small number of individuals causing pansynostosis and significant midface hypoplasia. 47 …”
Section: Signaling Bone Formationmentioning
confidence: 99%
“…These findings suggest that the range of bone phenotypes observed in CCD patients could be due to a quantitative reduction in the functional activity of RUNX2. By contrast a higher gene dosage due to mutations with excess copy of RUNX2 also causes craniosynostosis (CS) syndrome (Greives et al, 2013; Mefford et al, 2010), an opposite extreme syndrome for bone development compared to CCD. CS causes premature mineralization of the bone growth areas including suture and hypertrophic zone of long bones.…”
Section: Introductionmentioning
confidence: 99%